Synthetic and biophysical studies on the tridachiahydropyrone family of natural products - Powell, Kimberley Jade (2014)
This thesis primarily details synthetic and biophysical studies on the tridachiahydropyrone family of natural products. The general aim of this work was to explore an hypothesis regarding the location and function of these metabolites, isolated from sacoglossan molluscs. Specifically, it was hypothesised that tridachiahydropyrone is synthesised photochemically from linear polyene precursors via a selective double bond isomerisation-6pi electrocyclisation sequence which occurs within the cell membrane of the producing organism. Furthermore, it was postulated that this reaction sequence, and subsequent photochemical transformations of tridachiahydropyrone into the related products phototridachiahydropyrone and oxytridachiahydropyrone, serve to protect the producing mollusc from the damaging effects of UV radiation. Firstly, the proposed polyene precursors were synthesised using a convergent strategy dependent upon a late-stage Suzuki coupling. Their photochemical, biomimetic conversion into tridachiahydropyrone, phototridachiahydropyrone and oxytridachiahydropyrone, was then accomplished. The interactions of tridachiahydropyrone and its biomimetic precursors with model membrane systems were next explored, using a fluorescence spectroscopic technique. This work demonstrated that the molecules bind to phospholipid vesicles (PLVs) of varying compositions. The synthesis of tridachiahydropyrone within the PLVs was also achieved The propensity of the compounds to act as sunscreens was lastly investigated, by measuring the degree of protection against photochemically-induced lipid peroxidation they conferred on irradiated PLVs, using the thiobarbituric acid reactive substances assay. At high compound concentrations the compounds were found to act as sunscreens, whilst at lower concentrations pro-oxidant activity was observed. In addition to this main work, methodology for the palladium-catalysed cyanation of vinyl halides with acetone cyanohydrin was developed. Conditions were optimised using beta-bromostyrene, and shown to be applicable to a range of diverse substrates. The protocol proved chemoselective for vinyl bromides in the presence of aryl bromides, which were left unaffected and available for further chemical transformations, adding to the synthetic utility of the reaction.